Partida de um reator anaeróbio de fluxo ascendente com manta de lodo (UASB) no tratamento de efluentes provenientes de uma indústria de laticínios - Hamerski, Fernando (2012)
Surface Waters are generally used as support for disposal of waste generated by man. The effluents from dairy industries are characterized by high volume presents, but mainly because of its high concentration of organic load. The evolution of agro-industrial systems wastewater treatment offers the application of eficiente technologies of the environmental impact is kept to a maximum. The UASB (upflow anaerobib sludge blanket) reactor is considered one of the most representative anaerobic systems, due to its high biomass concentration and a rich microbial diversity. This study aimed to initiate and control their operation in the anaerobic digestion process to the treat wastewater from a dairy plant evaluating the removal of control parameters (temperature, pH, COD, BOD5, TKN, TS and VST) beside the design parameters (HRT, HLR and VOL). The reactor was operated with the HRT of 0,085 d-1, and VOLs ranging from 12,58 to 29,2 kg.m-3.d-1, which influenced the high HLR value. To start, the inoculum used was from a septic tank. The temperature oscillations due to the presented experimental period. As for the control parameters, the system showed a significant difference in the removal of organic matter. The removal of BOD5 by the system obtained a removal efficiency of 42,7%. For COD, removal was 58,6%. The removal efficiency was related by large sludge production, indicating the time of withdrawal of excess. The concentration of excess sludge was analyzed, which showed significant 17.538 mg.L-1, being the explicit need for disposal of the sludge during operation.